Bis[2-(4,5-diphenyl-1H-imidazol-2-yl)-4-nitro-phenolato]copper(II) dihydrate: crystal structure and Hirshfeld surface analysis - Chettri, Sailesh; Brahman, Dhiraj; Sinha, Biswajit; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2019)
The crystal and molecular structures of the title CuII complex, isolated as a dihydrate, [Cu(C21H14N3O3)2]2H2O, reveals a highly distorted coordination geometry intermediate between square-planar and tetrahedral defined by an N2O2 donor set derived from two mono-anionic bidentate ligands. Furthermore, each six-membered chelate ring adopts an envelope conformation with the Cu atom being the flap. In the crystal, imidazolyl-amine-N—HO(water), waterO—HO(coordinated, nitro and water), phenyl-C—HO(nitro) and (imidazolyl)–(nitrobenzene) [inter-centroid distances = 3.7452 (14) and 3.6647 (13) A˚ ] contacts link the components into a supramolecular layer lying parallel to (101). The connections between layers forming a three-dimensional architecture are of the types nitrobenzene-C—HO(nitro) and phenyl-C—H(phenyl). The distorted coordination geometry for the CuII atom is highlighted in an analysis of the Hirshfeld surface calculated for the metal centre alone. The significance of the intermolecular contacts is also revealed in a study of the calculated Hirshfeld surfaces; the dominant contacts in the crystal are HH (41.0%), OH/HO (27.1%) and CH/HC (19.6%).